Analisa Kandungan Boraks pada Tahu dengan Menggunakan Texture Analyzer dan Spektrometer - Putro, Permono Adi; Susanti, Novita Dwi; Wulandari, Devia Putri (Jurnal Riset Fisika Indonesia, 2025)
Food safety is a critical issue in ensuring public health, especially in preventing contamination from harmful substances illegally added to food. One such hazardous additive is borax, which is sometimes used by unscrupulous food producers to preserve texture and shelf life, despite its known toxicity and prohibition in food products. This study aims to detect the presence of borax in tofu, a widely consumed protein source, by utilizing two analytical tools such as a Texture Analyzer and a Spectrometer. The Texture Analyzer was employed to evaluate the physical firmness of tofu, as borax is known to increase its hardness. The Spectrometer was used to confirm the chemical presence of borax. Results indicated that tofu samples containing borax showed significantly firmer textures compared to control samples, and the spectrometric analysis successfully detected borax compounds. These findings demonstrate that both instruments are effective in identifying borax contamination. The study recommends the sustainable development of rapid and accurate detection methods for other hazardous additives to enhance food safety monitoring and enforcement practices.